Positive Reaction to Accounting Restatement: The Episode of Reasons and Earning Changes - Dian Nurmala Dewi (Politeknik Negeri Lampung, 2014)
The research about market reaction toward accounting restatement indicated different facts from previous research. Markets react positively. This fact called for further research related to market reaction by involving the causes and effects of restatement on the profit element. Hence, the research was aimed at reevaluating the difference of market reaction toward accounting restatement which is distinguished based on the causes of the restatement and their effects on the profit. To reach the goal, the research conducted significance of market reaction measured with abnormal return (AR) and market reaction difference tests measured by cumulative abnormal return (CAR). The samples were taken from the restatement occurred from 2009-2012, with occurrence period of 5 days around the dates. There were 63 events taken as the samples. The result of the test shows that market reacted differently when there were differences of the causes and effects of the profit. The finding indicate that the information related to the reasons of restatement and the change of the profit as the result of the restatement are different aspects to identify. In the test group, it was indicated that the market tended to react more when the restatement was based on the basic error and the restatement causing profit increase. More specific research may provide clearer understanding related to the Indonesian stock exchange characteristics in responding to accounting restatement.Keywords : accounting restatement, causes of restatement, profit change, market reaction